Characteristics of methyl cellulose-NH4NO3-PEG electrolyte and application in fuel cells - Shuhaimi, N.E.A.; Alias, N.A.; Kufian, M.Z.; Majid, Siti Rohana; Arof, Abdul Kariem (Springer Verlag (Germany), 2012)
We report the viability of methyl cellulose (MC) as a membrane in a polymer electrolyte membrane fuel cell (PEMFC). Methyl cellulose serves as the polymer host, ammonium nitrate (NH4NO3) as the doping salt and poly(ethylene glycol) (PEG) as plasticizer. Conductivity measurement was carried out using electrochemical impedance spectroscopy. The room temperature conductivity of pure MC film is is (3.08 +/- 0.63) x 10(-11)S cm(-1). The conductivity increased to (2.10 +/- 0.37) x 10(-6)S cm(-1) on addition of 25 wt.% NH4NO3. By adding 15 wt.% of PEG 200 to the highest conducting sample in the MC-NH4NO3 system, the conductivity was further raised by two orders of magnitude to (1.14 +/- 0.37) x 10(-4)S cm(-1). The highest conducting sample containing 15 wt.% PEG was used as membrane in PEMFC and was operated at room and elevated temperatures. From voltage-current density characteristics, the short circuit current density was 31.52 mA cm(-2) at room temperature (25 degrees C).